La presenza subalterna in Italia e la scrittura come terapia - Reichardt, Dagmar (Incontri. Rivista europea di studi italiani, 2013)
From a theoretical and social point of view, modern Italophone postcolonial writing relegates to ways of receiving reality in the tradition of Verism and Neorealism,especially if aspects of violence are being considered. Notably the texts of female immigrant writers represent the subaltern (Gayatri C. Spivak) as they reflect thebiographical traumatic experiences of their authors or historical violent backgroundsof the plots. In this sense, according to the paradigm of James W. Pennebaker (Writing Therapy), writing often assumes a therapeutical function. This article recalls the first attempts of articulating the Italian colonial past in literature, starting with Ennio Flaiano and Mario Tobino, and then focusing on the innovative migratory texts of female Italophone writers from the 1990s onwards, namely those of Ribka Sibhatu,Cristina Ali Farah, Gabriella Ghermandi and Igiaba Scego who culturally speaking all originate from former Italian colonies in Africa. By making use of the theorems ofArmando Gnisci and Dacia Maraini, it becomes evident how female Italophone migrant writing must be recognized not only as a process of sensitization, but also asillness and therapy at the same time. Thus, the act of writing creates a transculturalspace of both conflict and encounter, in which a talking back from the periphery of Italian society takes place, with the effect of reconciling Italy with its colonialhistory and globalized present.